Paternal Social Determinants of Childhood Mortality in Zimbabwe - Laston Gonah; Dumisani Sibanda; Sibusiso C Nomatshilla (Annals of Global Health)
Introduction: In Zimbabwe, studies have mainly focused on child and maternal factors contributing to under-5-year mortality, and little has been published concerning the paternal social determinants, which are also important. Aim: The goal of this paper is to investigate the paternal social determinants of infant and childhood mortality in Zimbabwe. Methods: The study analyzed cross-sectional secondary data from the Zimbabwe Demographic Health Survey (ZDHS) 2015 to investigate paternal determinants of infant and child mortality. Multivariate logistic regression and Cox regression were conducted for separate analyses of infant and child data to determine the odds and risk of death informed by paternal factors. Kaplan–Meier survival curves were used to determine the importance of paternal factors in determining under-five survival. Results: Younger paternal age, lower level of education, lower wealth index, unemployment, and rural geographical location are important contributing factors for childhood mortality, and these factors were found to be interconnected and interrelated in producing the observed outcomes. Conclusion: Paternal characteristics are important contributing factors for child survival, but not alone. The interaction between child characteristics, household (paternal and maternal), community, and public/global-policy-level factors is important in shaping observed childhood mortality outcomes. Social determinants for child survival are interlinked and interdependent on each other in producing the observed childhood mortality outcomes, and no one factor is more important than the other. Each factor represents an important component but not one that is individually sufficient to produce an outcome.